An enhanced component based model for steel connection in a hybrid coupled shear wall structure: Development, calibration and experimental validation. (November 2016) - Morelli, F.; Manfredi, M.; Salvatore, W.
Highlights: The definition of a component-based model for HCSW coupling system is proposed. The main components are individuated on the base of experimental evidences. Calibration of components is based on experimental results available in literature. Experimental setup and results are described in details. The comparison with the experimental result highlights the reliability of the model. Abstract: In the present paper the development, calibration and experimental validation of two component-based models of dissipative steel links connecting a reinforced concrete wall to a steel gravity frame is presented. The dissipative capacity of such structures is greatly influenced by the effective hysteretic behavior of the wall-to-column coupling system. Within the present work, experimental tests results on two different configurations of wall-to-column coupling system are presented. The development and calibration of two non-linear cyclic component-based models, one for each configuration, are described, allowing a better understanding of the force transmission mechanisms and their influence on the global structural behavior.